Validation of an ultrasensitive LC–MS/MS method for PTH 1–34 in porcine plasma to support a solid dose PK study. (July 2015) - Kay, Richard G; Hands, Jonathan T; Hawthorne, Glen; Constable, Scott; Grosvenor, Martin; Sharman, Johannah A
Background: The bioanalysis of Teriparatide (PTH 1–34) is extremely challenging due to the low plasma concentrations present at a therapeutic level. An LC–MS/MS-based method was developed that detected PTH 1–34 at 15 pg/ml in porcine plasma, and was validated using the bioanalytical method validation guidelines.Results: The analytical methodology demonstrated good linearity over a range of 15–1000 pg/ml, and demonstrated good precision and accuracy. The validated method was used to support a trial comparing a solid state dose to a solution-based injection (Forteo™).Conclusion: The ability to quantify the peptide at low pg/ml in porcine plasma demonstrates that it is possible to develop very sensitive LC–MS/MS-based methodologies to support the bioanalysis of large peptide biotherapeutics.